The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1007/bf02123497
|View full text |Cite
|
Sign up to set email alerts
|

Active immunization with feline leukemia virus envelope glycoprotein suppresses growth of virus-induced feline sarcoma

Abstract: The efficiency was examined of immunization with feline leukemia virus glycoprotein complexes (gp85 rosettes) to protect cats against tumors induced by feline sarcoma virus (FeSV). The glycoprotein was isolated from feline leukemia virus (FeLV). Young cats were vaccinated with the purified viral glycoprotein and challenged with FeSV (FeLV). FeLV gp85 antibody levels were measured by enzyme-linked immunosorbent assay and tumor volumes were determined. In immunized animals tumor development was reduced. Gp85 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…The latter two were quite faint. This observation suggested that the radioiodinated gpl2O preparation contained partially degraded gpl2O molecules in agreement with previous o'bservations (15 (27)(28)(29)(30)(31). Extensive experience in the production of large quantities of HIV has shown that purified virion preparations contain many contaminating cellular proteins and very little gpl20.…”
Section: Resultssupporting
confidence: 88%
“…The latter two were quite faint. This observation suggested that the radioiodinated gpl2O preparation contained partially degraded gpl2O molecules in agreement with previous o'bservations (15 (27)(28)(29)(30)(31). Extensive experience in the production of large quantities of HIV has shown that purified virion preparations contain many contaminating cellular proteins and very little gpl20.…”
Section: Resultssupporting
confidence: 88%
“…Thus neutralizing antibodies administered by serotherapy (Hunsmann et al, 1975) or induced by vaccination (Hunsmann et al, 1981) can protect animals against virus-induced Friend-erythroleukaemia and feline sarcoma (Hunsmann et al, 1983). After infection glycoproteins evoke the highest titre of antiviral antibodies (Ihle & Hanna, 1977).…”
Section: Shedding and Interspecies Type Sero-reactivity Of The Envelomentioning
confidence: 99%
“…coworkers (1975, 1981) have inm~nized mice against Friend marine leukemia virus using purified viral envelope proteins gp71 or gp85 complexes. A similar preparation, FeLV-gp85, has been used to immunize cats against Snyder-Theilen fibrosarcoma virus (ST-FeSV) induced tumors (Hunsmann et al, 1983). Feline leukemia virus-gp85 was immunogenic in cats, and inm~mized cats developed smaller tumors than non-vaccinated animals.…”
mentioning
confidence: 99%